Relações filogenéticas da subfamília Didelphinae: padrões de variação da morfologia crânio-dentária (Marsupialia: Didelphidae) - Camardella, Arianna Rocha (1999)
Used a cladistic analysis to evaluate the phylogenetic relationships among living and fossil genera of the Subfamily Didelphinae. Four different genera were used as outgroups: Caluromys (Caluromyinae, Didelphidae), Sparassocynus (Sparassocynidae), Caenolestes (Caenolestidae) e Dromiciops (Microbiotheriidae). A total of 146 cranial and dental characters were utilized in the analysis, that was performed using the branch swapping m* bb* option of the program Hennig86. Three most parsimonious trees (consistency índex 0,56 and retention index 0,83) were found after applying successive weighting to the analysis with Dromiciops as the outgroup, comprising, thus, the totality of characters and taxa examined. All analyses yielded cladograms with similar topologies, showing two main clades. The first clade included all small didelphids, with exception of Lestodelphys e Monodelphis: (Micoureus (Marmosa (Marmosops (Gracilinanus, Thylamys)))). The second clade encompassed Lestodelphys, Monodelphis, the fossil taxa (Thylophorops, Hyperdidelphys, Thylatheridium e Zygolestes), and all the large didelphids (Lutreolina (Chironectes (Didelphis, Philander))), but the phylogenetic relationships between these branches are still unclear. Furthermore, the genus Metachirus showed an ambiguous position in relation to these two main clades. These results corroborate the monophyly of the large didelphids (Tribe Didelphini sensu McKenna & Bell, 1997), but they dispute the proposal that all small didelphids form a monophyletic group (Tribe Monodelphini sensu McKenna & Bell, 1998).